MANAJEMEN PERPUSTAKAAN DALAM RANGKA MENINGKATKAN PRESTASI AKADEMIK DI MADRASAH ALIYAH NEGERI YOGYAKARTA III (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
This research aims to describe the management of library in order to increase the academic achievement in MAN Yogyakarta III which include : (1) planning of library management, (2) organizing of library management programm, (3) the implemetation of library management programm,and (4) evaluation of library management program. This is a qualitative research. MAN Yogyakarta III was choosen as the research sitebecause this library school had got the first champion in national library competition. Data collecting method was conducted by means of observation, interview, and documentation. Milesand Huberman’s model of qualitative data was used to analyze it . The result of the research shows that the library management in MAN Yogyakarta III has been well managed. Students had been motivated to use all facilities in this library. They like to read and discussion in the library, because the room was so comfortable that they like to study there. Involvement of all person in this school can be shown in library management, they keep in pleasure, cleanliness, care of books, used them carefully, and encourage any programms was hold by the library. Library existance has been complete and has some interesting programms that can influence the increase of student’s academic achievements. Based on observation, there is a significant increasing in student’s academic achievement in MAN Yogyakarta III after the management has beenmanaged well. In fact, after the library has got the winner in national library competition, students academic achievements increase deeply. So, the existance of library must be kept, and more rised up in the management, so that it can be more and more useful to any person.